Optimalisasi Penulisan Artikel Ilmiah Untuk Mendukung Publikasi Pada Jurnal Terindeks Science And Technology Index (SINTA) Level 4 - Siti mahfudhoh; B.Herawan Hayadi; Miftahul Ilmi; Natis Sutisna; siti salbiah; Akhmad jonny irawan (Jurnal Ilmiah Pendidikan dan Keislaman, 2026)
A systematic and strategically written scientific article is a key factor in successful publication in journals indexed in SINTA 4. This study aims to analyze the optimal steps for writing scientific articles, including topic selection, title and abstract formulation, research methodology, as well as discussion and conclusion strategies. The research method used is descriptive qualitative with content analysis of 25 articles published in SINTA 4 journals during 2018–2025. The results indicate that articles with a clear structure, informative abstracts, valid methodology, and evidence-based discussion have a higher likelihood of acceptance. This study provides practical recommendations for authors seeking to improve their chances of publication in SINTA 4 journals.